PENGARUH CITRA MEREK DAN PERSEPSI KUALITAS TERHADAP NIAT BELI LAPTOP MEREK APPLE (Studi Pada Pengunjung Grand City Surabaya dan Delta Plaza Surabaya) - PRAMUGITHA, ARLENDRA (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this study was to examine the influence of brand image and perceived quality of the purchase intention. The sampling technique used is non - probability sampling and sampling conducted by judgmental sampling with a sample taken as many as 210 people. Target respondents are already understood laptop apple and twenty-five years and above. The scale of measurement in this study using a Likert scale. Measuring instrument used was a questionnaire. Analysis of data using multiple linear regression model. The results show there is influence brand image on the purchase intention and perceived quality on the purchase intention. It can be seen from these two variables contribute to the purchase intention of 34.5%. Keywords: Brand Image, Perceived Quality, Purchase Intention.